Antigen-specific B cells reactivate an effective cytotoxic T cell response against phagocytosed Salmonella through cross-presentation. - Jelle de Wit; Yuri Souwer; Tineke Jorritsma; Hanny Klaasse Bos; Anja ten Brinke; Jacques Neefjes; S Marieke van Ham (PLoS ONE, 2010)
BACKGROUND: The eradication of facultative intracellular bacterial pathogens, like Salmonella typhi, requires the concerted action of both the humoral immune response and the cytotoxic CD8(+) T cell response. Dendritic cells (DCs) are considered to orchestrate the cytotoxic CD8(+) T cell response via cross-presentation of bacterial antigens onto MHC class I molecules. Cross-presentation of Salmonella by DCs however, is accompanied by the induction of apoptosis in the DCs. Besides antibody production, B cells are required to clear Salmonella infection for other unknown reasons. METHODOLOGY/PRINCIPAL FINDINGS: Here we show that Salmonella-specific B cells that phagocytose Salmonella upon BCR-ligation reactivate human memory CD8(+) T cells via cross-presentation yielding a Salmonella-specific cytotoxic T cell response. The reactivation of CD8(+) T cells is dependent on CD4(+) T cell help. Unlike the DCs, B cell-mediated cross-presentation of Salmonella does not coincide with apoptosis. CONCLUSIONS/SIGNIFICANCE: B cells form a new player in the activation of the cytotoxic effector arm of the immune response and the generation of effective adaptive immunity in Salmonella infection.